Association between Physical Activity and Disability in patients with low back pain - Cristian Douglas Dantas de Sousa; Ana Carla Lima Nunes; Fabianna Resende de Jesus-Moraleida (Universidade Estadual Paulista (UNESP), 2017)
Abstract AIMS Physical activity levels could be related to chronic low back pain (LBP) in those who suffer from it; thus the purpose of this study was yo describe the physical activity levels in patients with chronic LBP, and to investigate whether physical activity levels are associated with LBP related disability and pain intensity in them. OBJECTIVES To describe the physical activity levels in patients with chronic LBP, and to investigate whether physical activity levels are associated with LBP related disability and pain intensity in them. METHODS This is a cross-sectional study with 36 patients with chronic LBP, both sexes, aged between 18 and 70 years. The main outcomes evaluated in this study were physical activity levels, LBP-related disability and pain intensity. RESULTS Participants were predominantly classified as active (53%) and irregularly active (42%). Mean pain intensity was 4.81 (± 2.72) points, while mean LBP-related disability was 13.19 (± 6.95). Physical activity and disability were negative and moderately correlated. CONCLUSION Physical activity and disability are inversely related, indicating that patients with chronic LBP that have lower physical activity levels had higher levels of disability.